2019
DOI: 10.1021/acssensors.9b01484
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Analyte Theft in Surface-Enhanced Raman Spectroscopy Substrates: Subnanomolar Quantitative Drug Detection

Abstract: Quantitative applications of surface-enhanced Raman spectroscopy (SERS) often rely on surface partition layers grafted to SERS substrates to collect and trap-solvated analytes that would not otherwise adsorb onto metals. Such binding layers drastically broaden the scope of analytes that can be probed. However, excess binding sites introduced by this partition layer also trap analytes outside the plasmonic “hotspots”. We show that by eliminating these binding sites, limits of detection (LODs) can effectively be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 54 publications
1
35
0
2
Order By: Relevance
“…The extreme sensitivity of surface-enhanced Raman spectroscopy (SERS) makes this technique a promising and powerful sensing platform. [1] With hardware components such as lasers and detectors rapidly reducing in cost, SERS has the potential to become an economically viable technique [2] with broad adoption in medical diagnosis, [2] environmental monitoring, [3] drug detection, [4] food quality control [5][6][7][8][9][10] and continuous health screening. [11] As first identified by Jeanmaire and van Duyne in 1977, this extraordinary sensitivity stems from the powerful field enhancements that can arise in nanostructured metal surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The extreme sensitivity of surface-enhanced Raman spectroscopy (SERS) makes this technique a promising and powerful sensing platform. [1] With hardware components such as lasers and detectors rapidly reducing in cost, SERS has the potential to become an economically viable technique [2] with broad adoption in medical diagnosis, [2] environmental monitoring, [3] drug detection, [4] food quality control [5][6][7][8][9][10] and continuous health screening. [11] As first identified by Jeanmaire and van Duyne in 1977, this extraordinary sensitivity stems from the powerful field enhancements that can arise in nanostructured metal surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] In a traditional clinical setting or at the point of care (POC) arena, many diagnoses require extremely short turnaround times from sample collection to an operational result. [20][21][22][23][24] Therefore a fast, sensitive, simple, and portable on-site analytical method is needed urgently to be developed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that the issues of poor reproducibility and weak signal intensity resulted from uncontrolled aggregations of colloidal Au NPs can be addressed by attaching macrocyclic molecules, cucurbit[n]urils (CBn where n = 5-8 and 10), onto the Au NP surface to form precise plasmonic nanojunctions with a controlled interparticle spacing. [29][30][31][32][33][34][35] The aggregation of Au NPs showing SERS signals can be checked directly by dark-and bright-field microscopy. 36 Furthermore, CBs, which are highly symmetric, rigid and Raman-active, can form host-guest complexes with small analyte molecules via encapsulation inside their hydrophobic cavity.…”
Section: Introductionmentioning
confidence: 99%
“…38 While there has been previous work on Au NP-CB SERS sensing, applications of this promising system in biosensing remain relatively limited in the literature. 33,35 For instance, there is only one illustrative example on using this promising system for multiplexed sensing of neurotransmitters in SU, which has left plenty of room for more application-oriented studies. 33 Herein, we report the host-guest complexation between CB7 and an important biomarker, CRN, and the quantitative detection of CRN in water and in diluted SU using Au NP-CB nanoaggregates for the first time.…”
Section: Introductionmentioning
confidence: 99%